Directors of Kharkiv tractor plant: S.V. Salincov, P.Ya. Lisniak, M.A. Pashyn, P.Yu. Sablev - N. V. Pisarskaya (History of science and technology, 2018)
The given paper presents the main trends and results of the Kharkiv Tractor Plant directional staff activity namely S.V. Salenkov, P.Ya. Lisniak, M.A. Pashyn, P.Yu. Sablev for the period from 1940s up to 1960s. Peculiar features of S.V. Salenkov`s activity who was the first director of the plant after its re-evacuation and his contribution to the plant functioning are determined a special attention  is paid to the important role of P.Ya. Lisniak connected with the implementation of new technological items, achievement of full production resulted in the increase of qualified workers and specialists quantity. Attention is focused on M.A. Pashyn`s activity which key evidences is a manufacture of military machinery and equipment. The importance of P.Yu. Sablev`s activity influence as a chief who promoted to the manufacture of new machinery at the enterprise and its global reach is found. More than 100.000 T-54 tractors, the manufacture of caterpillar tractors T-74 and light artillery prime-mover was set up under the guidance of P.Yu. Sablev.